New perspectives on later life learning in the age of longevity - Withnall, Alexandra (Adult Education Discourses, 2023)
Recent decades have witnessed the ageing of populations in many countries across the world accompanied by unprecedented social, cultural, and technological change as well as recognition of the implications of climate change. As this demographic transformation has posed a full range of challenges to policy dimensions in certain countries, the importance of older people being able to access appropriate learning opportunities has become more widely recognised. Increasingly, it is understood that this is necessary not only for the economies of different countries, which may require people to remain for longer in the labour market but also as an essential component of a fulfilling later life. However, a focus only on chronological age and ageing fails to allow for the more positive aspects of what may be termed “the longevity effect” which has been driven by a better understanding of the factors that influence increased life expectancy in different countries, enabling people to live longer, happier and more productive lives. It is argued firstly that we need to rethink the current focus on “aging” and replace it with a more positive emphasis on “longevity” that includes an understanding of what happens to our brains as we grow older. Secondly, the concept of “long life learning” which is beginning to appear in different contexts is explored. Thirdly, it is acknowledged that the worldwide spread of COVID-19 has both opened up some novel ways of helping some older people to learn and, simultaneously, widened the so-called digital divide. Finally, the pernicious influence of ageism is considered.